Immune. : A journey into the mysterious system that keeps you alive. - Dettmer, Philipp, ....- (London : Hodder & Stoughton, 2021)
In Immune, Philipp Dettmer takes readers on a journey through the fortress of the human body and its defences. There is a constant battle of staggering scale raging within us, full of stories of invasion, strategy, defeat, and noble self-sacrifice. In fact, in the time you've been reading this, your immune system has probably identified and eradicated a cancer cell that started to grow in your body. Challenging what you know and think about your own body and how it defends you against all sorts of maladies and how it might also eventually be your own downfall, Immune is a vital and remarkably fun crash course in what is arguably, and increasingly, the most important system in the body.
Includes index.
Includes link to online bibliography.